Increased Participation Among Cleaners as a Strategy to Improve Quality and Occupational Health - Öhrling, Therese (Nordic Journal of Working Life Studies, 2014)
Like many other industries, today the cleaning industry is affected more than ever by competition and pressure toward low prices, which leads to a nonadvantageous situation for cleaners. These days many Swedish municipalities choose to outsource cleaning service in order to save money, although the situation for the cleaners appears to be worsening. The aim of this paper is to evaluate an alternative organizational structure within a Swedish public cleaning division to investigate how good work environment for cleaners can be combined with economical savings for a municipality. Like many other cleaning organizations, both national and international, the present cleaning division has been struggling for a long time with high levels of sick leave and early retirements. After years of unsuccessful attempts to improve the situation by reducing the physical load, cleaning managers made a decision to broaden their strategy by changing the structure of their organization. In this study, both qualitative and quantitative methods have been applied to identify and understand the effects of the organizational change, both on an individual level and on an organizational level. The results show that the organizational change, which leads to increased participation and autonomy for the cleaners, in combination with a high degree of social support, had a positive effect on job satisfaction, work motivation, and pride among the cleaners. Sick leave within the division has decreased, and both the quality and efficiency of the cleaning service have increased. It can be concluded that there are other alternative organizational structures that could be applied within the public sector and prove advantageous, both for the individual cleaners and for the municipality. Further research of similar organizational structures within the private cleaning sector is recommended.